2012
DOI: 10.1103/physrevb.86.094435
|View full text |Cite
|
Sign up to set email alerts
|

Heliconical magnetic order and field-induced multiferroicity of the Co2Y-type hexaferrite Ba0.3Sr1.7

Abstract: Using magnetoelectric measurements and neutron diffraction, we investigated multiferroic properties of Co 2 Y hexaferrite Ba 0.3 Sr 1.7 Co 2 Fe 12 O 22 in zero and finite magnetic field (H ⊥ c). Upon zero-field cooling, a longitudinal heliconical magnetic structure was observed below 280 K, which involves incommensurate planar helical ordering. When the magnetic field was applied perpendicular to its c axis, electric polarization was observed and the incommensurate ordering was replaced by a commensurate one a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 29 publications
1
25
0
Order By: Relevance
“…All transition temperatures increase with increasing Co content, which results from the fact that Co 2? ions can contribute to the enhancement of the magnetic ordering temperatures [40]. However, for x = 0.8 sample, the magnetic transition temperature T 2 is less than that for the x = 0.4 sample.…”
Section: Magnetic Studiesmentioning
confidence: 77%
“…All transition temperatures increase with increasing Co content, which results from the fact that Co 2? ions can contribute to the enhancement of the magnetic ordering temperatures [40]. However, for x = 0.8 sample, the magnetic transition temperature T 2 is less than that for the x = 0.4 sample.…”
Section: Magnetic Studiesmentioning
confidence: 77%
“…The latter is likely to correspond to the magnetic transition from the collinear ferrimagnetic to the spiral magnetic structure. 8,39 T N and T S were derived from the inflection points defined by the minimum of dM/dT from the M-T curve. Fig.…”
Section: E Magnetic Propertiesmentioning
confidence: 99%
“…Recently, Lee et al 8 found that Sr-doped single crystalline Co 2 Y ferrite exhibits a longitudinal conical magnetic structure below 280 K upon zero-field cooling. Such spin structure is able to turn into transverse conical (or slanted conical) magnetic structure under a magnetic field and hence the electric polarization can be produced according to the inverse Dzyaloshinskii-Moriya mechanism or spin current model.…”
Section: Introductionmentioning
confidence: 99%
“…5 6 It was revealed that the magnetically controllable ferroelectricity can be induced with a complicated cycloidal spin order in certain hexaferrites, which has been well described with the spin current model or inverse Dzyaloshinskii-Moriya interaction model. 1,[6][7][8][9] In these spiral magnets, the magnetic order and ferroelectricity are inherently coupled and thus pronounced ME effects could be expected. Such spiral magnetic order induced multiferroicity and ME effects have been extensively reported in transition metal magnates (e.g.…”
Section: Introductionmentioning
confidence: 99%